An active biomonitoring approach using three-spined stickleback (Gasterosteus aculeatus, L.) to assess the efficiency of a constructed wetland as tertiary treatment of wastewater. (July 2020) - Catteau, Audrey; Bado-Nilles, Anne; Beaudouin, Rémy; Joachim, Sandrine; Palluel, Olivier; Turiès, Cyril; Galet, Christophe; Geffard, Alain; Porcher, Jean-Marc
Graphical abstract: Highlights: Stickleback biomarker responses are altered downstream wastewater effluent 1. Effects on biomarker responses are reduced at the exit of a constructed wetland 2. The efficiency of a constructed wetland is highlighted 3. Active biomonitoring and IBR index are relevant tools for water quality assessment. Abstract: The present work aimed to assess the efficiency of a constructed wetland as tertiary treatment on urban wastewater with a multibiomarker approach using caged three-spined sticklebacks ( Gasterosteus aculeatus L. ). Fish were caged on three sites: at the entrance of the Constructed Wetland (CW), directly inside the wastewater effluent, at the exit of the CW, and in a weakly impacted site considered as a reference. After 21 days of caging, sticklebacks state of health was assessed using several biomarkers representing some biological functions such as innate immune and antioxidant systems, biotransformation enzymes, reproduction parameters and synaptic transmission. A strong inhibition of the innate immune system, an induction of EROD activity and an alteration of the hepatosomatic index were observed in fish caged at the entrance of the CW compared to those caged in the reference site. In addition, wastewater effluent induced a decrease of antioxidant system without induced oxidative damage on cell membranes. No improvement of these biomarkers was observed for antioxidant parameters at the exit of the CW. However, in fish caged at the exit of the CW, the EROD induction observed at the entrance was reduced and the innate immune system presented the same level compared to fish caged in the reference site, underlying the beneficial effect of the CW for these parameters. Integrated Biomarker response (IBR) was equal to 25.2 at the entrance of the CW and 17.4 at the exit of the CW which highlighted the global positive effect of the CW on water quality based on fish biomarker measurement.